2014
DOI: 10.1002/jcp.24729
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα and the Vitamin D Receptor Cooperate in the Regulation of Cathelicidin in Lung Epithelial Cells

Abstract: 1,25-Dihydroxyvitamin D3 (1,25(OH)2D3) and the vitamin D receptor (VDR) have been reported to have an important role in the regulation of innate immunity. We earlier reported that the antimicrobial peptide cathelicidin is induced by 1,25(OH)2D3 in normal human bronchial epithelial cells with a resultant increase in antimicrobial activity against airway pathogens. In this study, we demonstrate that C/EBP alpha (C/EBPα) is a potent enhancer of human cathelicidin antimicrobial peptide (CAMP) gene transcription in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Several reports suggested that Jmjd3 plays a role in general chromatin remodeling28 via interaction with an ATPase subunit of the SWI/SNF chromatin remodeling complex, Brg12829 and this interaction occurs in histone demethylase-independent manner. Moreover, the interaction between C/EBPα and SWI/SNF complex has also been described30313233. Indeed, we found that both Brm and Brg1 exhibited a promoting effect on HBV transcription (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Several reports suggested that Jmjd3 plays a role in general chromatin remodeling28 via interaction with an ATPase subunit of the SWI/SNF chromatin remodeling complex, Brg12829 and this interaction occurs in histone demethylase-independent manner. Moreover, the interaction between C/EBPα and SWI/SNF complex has also been described30313233. Indeed, we found that both Brm and Brg1 exhibited a promoting effect on HBV transcription (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Human SWI/SNF complexes, required for a wide variety of transcriptional programs during development, consist of ~15 subunits and contain Brg1 or Brm exclusively as the ATPase subunits454647. Moreover, the physical and functional interaction between C/EBPα and SWI/SNF complexes had also been documented303248. In hepatocytes, the ATPase subunit of SWI/SNF complex, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…18,29 Notably, these pathways are involved in enhanced expression of LL-37. 30,31 Here, we have demonstrated that LL-37-mediated autophagy requires intracellular calcium influx together with the signaling pathways AMPK and PtdIns3K downstream of the P2RX7 receptor. Together with calcium mobilization, these pathways are essential for the induction of the autophagy process in macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…While LL-37 exerts its antiviral activity via a direct effect on the virion in the case of this paper and others, cathelicidins in general (He et al, 2018) and LL-37 specifically (Barlow et al, 2014a) have also been shown to enhance other methods of innate antiviral immunity, namely interferon expression. Current work in endogenous antimicrobial peptide expression (Dhawan et al, 2015; Klein-Patel et al, 2006; Rivas-Santiago et al, 2005; Ryan et al, 2011; Ryan and Diamond, 2017) and small molecule mimetics of antimicrobial peptides (Beckloff et al, 2007; Menzel et al, 2017; Ryan et al, 2014) would potentially serve as methods to prevent not only KSHV infection, but also other viral infections of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%